2023
DOI: 10.3390/biomedicines11041203
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Isoeugenol and Eugenol against Impaired Nerve Function and Inflammatory and Oxidative Mediators in Diabetic Neuropathic Rats

Abstract: Diabetic polyneuropathy is characterized by structural abnormalities, oxidative stress, and neuroinflammation. The current study aimed to determine the antinociceptive effects of isoeugenol and eugenol and their combinations in neuropathic pain resulting from streptozotocin (STZ)-induced diabetes and neuroinflammation. Female SD rats were categorized into normal control, diabetic control, and treatment groups. On the 28th day and 45th day, behavioral studies (allodynia and hyperalgesia) were performed to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…IE, widely utilized in the food industry, is acknowledged as an authorized substance in the National Food Safety Standard for the Use of Food Additives (GB2760-2014) [ 15 , 16 ]. Studies have reported that IE inhibits skin cancer cell proliferation [ 17 ] while displaying anti-inflammatory, antioxidant, and antibacterial properties [ 15 , 18 ]. IE demonstrates substantial potential in improving skin photoaging.…”
Section: Introductionmentioning
confidence: 99%
“…IE, widely utilized in the food industry, is acknowledged as an authorized substance in the National Food Safety Standard for the Use of Food Additives (GB2760-2014) [ 15 , 16 ]. Studies have reported that IE inhibits skin cancer cell proliferation [ 17 ] while displaying anti-inflammatory, antioxidant, and antibacterial properties [ 15 , 18 ]. IE demonstrates substantial potential in improving skin photoaging.…”
Section: Introductionmentioning
confidence: 99%